Sistem Pendukung Keputusan Seleksi Penerima Beasiswa Menggunakan Metode Hibrid Fuzzy-AHP dan MOORA pada Madrasah Ibtidaiyah - Riki Evendi; Ahmad Zulfan (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The selection of scholarship recipients in educational institutions often faces challenges in objectivity and transparency of the decision-making process. Manual selection processes are prone to assessor subjectivity and require considerable time. This study aims to develop a decision support system for scholarship recipient selection using hybrid Fuzzy-AHP and MOORA methods at Madrasah Ibtidaiyah Daarul Ishlah Batam. The Fuzzy-AHP method is used to determine criteria importance weights by handling uncertainty in pairwise comparison assessments, while MOORA is used to rank students based on multi-criteria values. The system is designed as a web-based application using Laravel framework with MySQL database. Assessment criteria include academic performance, parental income, number of family dependents, non-academic achievements, attendance, and behavior. Research data uses 20 students with 120 assessment data for 6 criteria. Fuzzy-AHP calculations produce criterion weights with a Consistency Ratio of 0.0481, indicating excellent consistency. MOORA calculations successfully generate student rankings with the highest Yi value of 0.234156 to the lowest of 0.089234. System validation using black box testing shows a 100 percent success rate. This system proves capable of providing objective, transparent, and measurable scholarship recipient recommendations to support madrasah management decisions.